Discussion - Of Mr. Wheeler's Paper on Pure Coal as a Basis for the Comparison of Bituminous Coals (see Trans., xxxviii., 621) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1909)
A. Bement, Chicago,Ill. (communication to the Secretary*):— Formerly it was the general practice of engineers to designate coal that is free from moisture and ash as " combustible," notwithstandirig that it contains oxygen and nitrogen. The origin of this practice was more particularly due to the requirements in connection with boiler-testing, which demanded a consideration of that portion of the fuel which took part in the combuition-process because results based on a unit of either moist or dry coal were not comparable, since both moisture and ash were recognized as variable quantities. Thus, a pound of " combustible " became a standard of value, and was treated as a constant before employing measurements of heating-power and calculating therefrom the percentage of efficiency. The recognition of this term " combustible " was an advance to be credited to the engineer rather than to the chemist, because the latter, not having to do with the interpretation of analyses in practice outside the laboratory, usually saw no reason for reporting results in terms other than those of the moist-coal composition. Some years ago I needed a table of fuel-composition in terms of moist, dry, moisture-free and ash-free coal, and of the combustible components. This table required the use of the word combustible in its proper sense, for the purpose of designating carbon, hydrogen, and sulphur, instead of including these three elements with oxygen and nitrogen, to which aggregate the term combustible was formerly applied. To make such a tabulation involved either the use of the inconvenient and cumbersome term, "ash- and moisture-free coal," or of some other representative term, and for this purpose I adopted the expression pure coal, which is short, simple, convenient, and technically correct. It is also harmonious, because it agrees